Using free radical polymerization and Mannich reaction, synthesis and characterization of cationic polyacrylamides having similar molecular weight but different charge densities - Shatat, Raid Saleh; Niazi, Shaik Kalimulla (European Journal of Chemistry, 2018)
Using free radical solution polymerization technique and Mannich reaction, five different polyacrylamides with similar molecular weight but variable charge densities were synthesized. High molecular weight polyacrylamides were synthesized using potassium persulfate and N,N,N’,N’-tetramethylethylenediamine system as initiators. This was achieved by increasing the concentration of acrylamide monomer. They were then characterized by infrared spectroscopy, viscosity measurements and glass transition temperature measurement. These compounds with various cationic charge densities from 48.2, 161.7, 355, 425 and 485 C/g were prepared through Mannich reaction. The results indicate, by increasing the acidity of the polyacrylamide solution using sulfuric acid, the pH of the polyacrylamide solution decreases correspondingly. As a result, the positive charges increased resulting in the enrichment of charge densities.